Pengaruh Pelatihan Caring terhadap Perilaku Memberikan Asuhan Keperawatan pada Mahasiswa Saat Rotasi Klinik di Politeknik Depkes Palangka Raya - Abu Bakar; Widyandana Widyandana; Rossi Sanusi (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2014)
Background: Evaluation and faculty development program for dental faculty at Muhammadiyah University of Yogyakarta are necessary to improve clinical teacher abilities in skills laboratory. The objective of this study is to conduct pilot study of training program on clinical skills laboratory instructors’ teaching abilities; to measure instructors’ teaching ability before and after the training; and to understand instructors’ perception on the given training.Method: This study was a pretest-posttest single group design accompanied with qualitative method. The subjects are 12 clinical teachers and 91 students of Dental School, Muhammadiyah University of Yogyakarta. Quantitative data analysis by measuring effect size. Focus group discussion conducted after quantitative data were collectedResult: (1) There were moderate effect of clinical skills laboratory teacher’s training program to communication and clinical teaching abilities (d> 0,50). (2) The qualitative analysis showed the good perception of participants and feasibility of teacher training program, the lack of teacher of teacher training program, and the advice to improve the quality of teacher training program. Conclusion: Training of skills-lab instructors was needed to improve communication and teaching ability among skills-lab instructors.